Organic Syntheses 2005
DOI: 10.1002/0471264229.os081.21
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Primary Alcohols to Carboxylic Acids with Sodium Chlorite Catalyzed by TEMPO and Bleach: 4‐Methoxyphenylacetic Acid

Abstract: 4‐Methoxyphenethyl alcohol 4‐Methoxyphenylacetic acid 2,2,6,6,‐Tetramethyl‐1‐piperidinyloxy (TEMPO) Sodium hypochlorite

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 12 publications
1
33
0
1
Order By: Relevance
“…[c] [19] Simply changing chiral amine catalyst to ent-5 a for the catalytic enantioselective allylation reaction step consequently gives access to ent-12 o. We also wanted to investigate the importance of degassing the solvents prior to the co-catalytic enantioselective reaction and found that this was not the case (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…[c] [19] Simply changing chiral amine catalyst to ent-5 a for the catalytic enantioselective allylation reaction step consequently gives access to ent-12 o. We also wanted to investigate the importance of degassing the solvents prior to the co-catalytic enantioselective reaction and found that this was not the case (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…in aqueous acetonitrile. [42] TEMPO in combination with NaOCl generates the oxoammonium salt, which oxidizes the alcohol to the corresponding aldehyde as described above. In a subsequent process the aldehyde further reacts with NaOCl 2 to give the acid and NaOCl, which eventually acts as the oxidant in the reaction with TEMPOH to regenerate TEMPO + (10).…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…In each of these contributions, concise but thorough discussions of the following methods are given: (1) the preparation of a specific oxoammonium salt ([TEMP=O] + [BF 4 ] − ) and its use for the oxidation of geraniol; 12 (2) nitroxidecatalyzed oxidations using sodium hypochlorite; 13 (3) nitroxide-catalyzed oxidations using a catalytic amount of sodium hypochlorite with sodium chlorite as the secondary oxidant; 14 and (4) nitroxide-catalyzed oxidations using bis(acetoxy)iodobenzene (PhI(OAc) 2 ) as the secondary oxidant. 15 Comprehensive reviews have appeared on the chemistry of oxoammonium salts 10,16 -20 and on oxoammonium ion reactions.…”
Section: Introductionmentioning
confidence: 99%